Build location apps on iOS with Swift : use Apple Maps, Google Maps, and Mapbox to code location aware mobile apps - Linwood, Jeffrey (Apress, 2020)
Work with Apple Maps, Google Maps, and Mapbox in iOS with Swift programming. Guided by practical examples, this book covers all three map frameworks to ensure you properly select which one best suits your iOS app's needs in working with iOS location. You'll see how Apple's privacy settings apply to a user's location, and how to access that user's location from an application. Once you have access to the user's location, allow your app to display points of interest from Apple's database on the map inside the app, as well as to provide a search through that database by name. You can also incorporate turn by turn directions inside your own app to provide routes. Or trigger different functionality or notifications based on locational queues. With Build Location Apps on iOS with Swift, you'll even find out how to provide offline map support for hiking, camping, or other outdoors applications where cell phone service is weak. You will: Display points of interest within your own app Work with Apple's privacy settings so pertinent information comes through Trigger functionality based on geographic prompts Create your own custom map styles with Mapbox Studio and display them in the app.